Growth crisis in the EU: Challenges and prospects - Péter Halmai; Viktória Vásáry (Intereconomics, 2010)
The following article uses a production function approach to analyse the long-term trends of the European growth potential. It describes the possibility of a further significant decline in the potential growth rate and the mechanisms of this decline. EU Member States are divided into five country groups, and the potential growth rates of each of these as well as the contribution of different growth factors are analysed. The great challenges facing the 'catch-up' (Mediterranean and new) Member States with regard to convergence are outlined. Finally, the paper summarises the long-term trends, the impacts of potential shock scenarios on potential growth and the new risks originating from the crisis.
Keywords: 330